O método potenciométrico na determinação do H+ trocável em solos - Bergamin Filho, H.; Catani, R. A.; Petrin Junior, H. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
For the determination of exchangeable hydrogen ion in soils, the authors of the presente work made the extraction with normal calcium acetate solution that may have an initial pH between 7 and 8 without altering the amount of hydrogen ion extracted. The extraction was made by shaking 5,0 grams of air dry soil with 100 ml of normal calcium acetate solution, the pH of wich was ascertained to 7,0, 7,5 and 8,0 with acetic acid, in 250 mil conical flasks for 30 minutes in a Wagner shaker (30-40 rpm). The contents of the flasks were then, filtered. A 50 ml aliquot of each of the leachate was titrated with a 0,020 N NaOH solution and the volumes consumed sodium hydroxide were ploted against pH. The titration curves thus obtained showed to be straight lines between pH 8 and 9 and parallel to the curve obtained by the titration of the blank. Two ways of locating the end point of the titration showed to be possible: the use of a pHmeter or titrimeter or the use of phenolphtalein as indicator. When using a pH meter or a titrimeter, the end point may rest in any point between pH 8 and 9, and the volume of sodium hydroxide consumed is found by comparison with a similar curve obtained by the titration of the blank. When using phenolphtalein the calcium acetate solution must have a pH below 8.